2017
DOI: 10.19094/contextus.v15i3.961
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade da educação nas escolas públicas no Brasil: uma análise da relação investimento por aluno e desempenho nas avaliações nacionais

Abstract: Neste artigo, adotou-se a perspectiva econômica da educação. Esta abordagem assume que a qualidade do ensino pode ser mensurada pela eficácia do uso dos recursos disponíveis. Assim, foi analisada a correlação entre investimento por aluno no ensino fundamental, de 2005 a 2015 (desde o início da série histórica à última avaliação), e os resultados do Índice de Desenvolvimento da Educação Básica (Ideb) de cada estado. Na análise por região (Norte, Nordeste, Centro-Oeste, Sudeste e Sul), as redes de ensino que mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 1 publication
0
2
0
2
Order By: Relevance
“…In Brazil, the investment on education grew 91% over the period from 2008 to 2017 and reached approximately 6% of its gross domestic product (GDP) (Brasil, 2018). Nevertheless, only the states of Minas Gerais, Pernambuco and Goiás show a positive correlation between primary school student learning improvement and the increase in investment per pupil from 2000 to 2015 (Moraes et al, 2017).…”
Section: Contextmentioning
confidence: 90%
“…In Brazil, the investment on education grew 91% over the period from 2008 to 2017 and reached approximately 6% of its gross domestic product (GDP) (Brasil, 2018). Nevertheless, only the states of Minas Gerais, Pernambuco and Goiás show a positive correlation between primary school student learning improvement and the increase in investment per pupil from 2000 to 2015 (Moraes et al, 2017).…”
Section: Contextmentioning
confidence: 90%
“…No entanto, não existe um consenso quanto a maneira, e grau de relação, que os recursos investidos nas unidades escolares influenciam o desempenho dos alunos em avaliações governamentais, o que torna necessária a inclusão de outras variáveis na análise (Altinok, 2008). Na pesquisa de Moraes et al (2017), eles avaliaram que o investimento explicava a melhoria nos índices de aprendizado até certo nível. Dessa maneira, os recursos investidos nas unidades escolares ... são necessários e podem explicar a melhoria dos índices de aprendizagem, mensurados pelo Ideb, até certo nível.…”
Section: Organizações E Sustentabilidadeunclassified
“…Majoritariamente, as pesquisas que utilizam os gastos optam por esse modelo por possibilitar fazer análises a nível macro, como comparar os recursos investidos em diferentes municípios (Dal Magro & Silva, 2016;Fabre et al, 2017;Faria et al, 2008;Lourenço et al, 2017;Monteiro, 2015;Moraes et al, 2017;Souza et al, 2015). No entanto, a utilização dos gastos como métrica para analisar os recursos investidos na educação, apesar de pertinente, acaba mascarando situações de desigualdade entre as escolas em uma análise minuciosa do nível micro conforme já apontado pelos estudos de Amâncio .…”
Section: Organizações E Sustentabilidadeunclassified
“…In Brazil, there are already some studies on the administration of basic education schools that seek to identify how school administrators collaborate to improve students' learning performance. Analyzing the correlation between investment per student in basic education (2005)(2006)(2007)(2008)(2009)(2010)(2011)(2012)(2013)(2014)(2015) and the results of the Basic Education Development Index, Moraes, Dias and Mariano (2017) showed that only three Brazilian states there is a correlation between improvement of student learning and increased investment per student. Meantime, the country, Brazil, cannot disseminate the best management practices found in these Brazilian states.…”
Section: Literature Reviewmentioning
confidence: 99%